Josie Weese: capstone - Weese, Josie, artist (Colorado State University. Libraries, 2025)
The artist's statement: As I have learned about the world of arthropods and entomology, I developed a profound sense of care for these often-overlooked creatures. I was taught that their survival is intricately tied to human actions—both on a micro and macro scale. Our relationship with insects has evolved through time and across cultures, and I aim to show that changing dynamic through my work. My intention is to invite you to reflect on how we interact with these creatures and recognize their vital role in our ecosystem. This is more than just an observation; it is a call to action, a plea for us to care about the world of insects and, by extension, the world around us.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: printmaking